Representation and muslim women athletes: A textual analysis of a Nike commercial - Alqahtani, Hessah; Campbell, Christopher (Eximia, 2022)
Women representation in the media remains a critical issue in the debate on gender equality. Due to religion and culture, Muslim women have been sidelined. This explains the low involvement of Muslim women in sports. This paper analyzes a 2017 ad by Nike, which highlights the issue of women's representation and position in society, especially by focusing on the activities presumed to be a preserve of the male gender. Specifically, the paper focuses on Muslim women athletes, given that they still face significant challenges based on masculine tendencies in the Muslim community. The denotative analysis reveals the role of culture and religion in suppressing women, especially by preventing women from participating in sports. The Nike video pre-empts the new developments in the Muslim community where women are now participating in sports, implying the impact of the feminist movement. A connotative analysis further revealed the role of religion and race in shaping women's welfare in society. Further analysis reveals that Muslim women suffering from gender oppressive tendencies despite the push for gender equality and equity through the fourth wave of feminism. Specifically, Muslim countries have laws that still impede women from achieving similar goals as men.